2018
DOI: 10.1002/pan3.5
|View full text |Cite
|
Sign up to set email alerts
|

Value diversity and conservation conflict: Lessons from the management of red grouse and hen harriers in England

Abstract: Conflicts between people over wildlife management are damaging, widespread, and notoriously difficult to resolve where people hold different values and worldviews. Cognitive approaches examining steps from human thought to action can help us understand conflict and explore strategies for their management. We focused on the conflict between hunters and conservationists over the management of red grouse (Lagopus lagopus scoticus) and hen harriers (Circus cyaneus) in the English uplands which represents a classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…We observed that gamekeeper professional identity was rooted in concepts of custodianship and that much predator control was undertaken with the objective of conserving game and non‐game wildlife. Where the objective is to build trust between stakeholders by identifying common narratives and goals (Hodgson et al., 2018; St John et al., 2019), we suggest that a focus on these relational values has the best chance of success. Similarly, focusing on the stewardship relationships that emerged from the professional identity and personal norm motivations might have merit where the goal is behavioural change for predator conservation as targeting these would ‘recognise and work within the boundaries of existing values’ (Manfredo, Teel, & Dietsch, 2016).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…We observed that gamekeeper professional identity was rooted in concepts of custodianship and that much predator control was undertaken with the objective of conserving game and non‐game wildlife. Where the objective is to build trust between stakeholders by identifying common narratives and goals (Hodgson et al., 2018; St John et al., 2019), we suggest that a focus on these relational values has the best chance of success. Similarly, focusing on the stewardship relationships that emerged from the professional identity and personal norm motivations might have merit where the goal is behavioural change for predator conservation as targeting these would ‘recognise and work within the boundaries of existing values’ (Manfredo, Teel, & Dietsch, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…One challenge, for example, would be that the personal enjoyment that motivates some predator removal is likely to be rooted in values that are not shared by all actors (Manfredo et al., 2017). Indeed, recent research from the uplands found that stakeholders on different ‘sides’ of conflicts over predators have divergent wildlife value orientations (St John et al., 2019). Yet, our findings also suggest there may be opportunities to mitigate social conflicts over predators by focusing on shared ‘relational values’ between stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, although different conservation managers and stakeholders are unlikely to always agree—for both practical and value‐based reasons (Rust ; St John et al. )—better understanding others’ positions and increasing dialogue helps foster more effective collaboration (Game et al. ; Lute et al.…”
Section: Discussionmentioning
confidence: 99%